2020
DOI: 10.1515/znc-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oils of three Malaysian Xylopia species (Annonaceae)

Abstract: The rich and diversified Malaysian flora represents an excellent resource of new chemical structures with biological activities. The genus Xylopia L. includes aromatic plants that have both nutritional and medicinal uses. This study aims to contribute with information about the volatile components of three Xylopia species essential oils: Xylopia frutescens, Xylopia ferruginea, and Xylopia magna. In this study, essential oils were extracted from the leaves by a hydrodistillation process. The identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The yield for the present samples is higher than that reported in the literature. Cascaes et al [ 3 ] and Shakri et al [ 34 ] obtained yields of 1.50% and 0.15%, respectively, for EO from the leaves of Xfru. These values indicate that the yield of the EO of Xfru in the present study is lower than that found by Cascaes et al [ 3 ] and considerably higher than that reported by Shakri et al [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The yield for the present samples is higher than that reported in the literature. Cascaes et al [ 3 ] and Shakri et al [ 34 ] obtained yields of 1.50% and 0.15%, respectively, for EO from the leaves of Xfru. These values indicate that the yield of the EO of Xfru in the present study is lower than that found by Cascaes et al [ 3 ] and considerably higher than that reported by Shakri et al [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cascaes et al [ 3 ] and Shakri et al [ 34 ] obtained yields of 1.50% and 0.15%, respectively, for EO from the leaves of Xfru. These values indicate that the yield of the EO of Xfru in the present study is lower than that found by Cascaes et al [ 3 ] and considerably higher than that reported by Shakri et al [ 34 ]. Such differences may be associated with several factors, such as the geographical location, seasonal and circadian cycles of the plants, stage of maturation of the specimens, and soil conditions [ 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation